Managing What You Cannot Measure: Anesthetic Implications of Takayasu’s Arteritis in Hypertensive Intracranial Hemorrhage - Mythreyi Muthukrishnan; Sasha Maria Menon; Niya Krishna; Sweekar Kudpi Shenoy (Annals of African Medicine, 2026)
Abstract Takayasu’s arteritis is a rare inflammatory vasculopathy affecting medium- and large-caliber arteries, often presenting as cerebrovascular incidents in young individuals, primarily due to uncontrolled hypertension. The following is the case of a young male with no known comorbidities who exhibited intracranial hemorrhage resulting from accelerated hypertension. The fundamental diagnosis of autoimmune arteritis concerning the aorta was determined during the perioperative phase. Emphasized are the challenges posed by uncommon etiologies of secondary hypertension in anesthetic and perioperative blood pressure management, especially in emergency situations, stressing the necessity of a heightened index of suspicion in young patients presenting with severe, refractory hypertension.